Describing Public Speaking Class Through Questioning Strategy at English Department UNTAG Banyuwangi: English - Saiful Anwar (JOEY: Journal of English Ibrahimy, 2023)
Public speaking becomes very influential aspect to everyone carrier such the aim to be an educator, a motivator, an entertainer and etc. Nevertheless, to become public speaker, there are some steps to be passed. One of them that he/she must has self-confidence to stand before audiences and not being nervous. This research is to retell students’ struggle while learning public speaking with their challenge that faced in every meeting. Researcher utilized qualitative narrative inquiry as the research methodology. This method constitutes as one that to tell everyone experience in life included in learning public speaking. Then, to collect data, researcher tended to use interview. It means the result of the research from the interview which made by researcher related to the class such the impression, preparation, something that makes students nervous as well as the hope after following the class. The result showed that students really enjoyed the class and really involved in the class. It is because they are really like the class and the strategy in carrying the class match to the materials. In conclusion, students are able to perform as public speaker before others confidently although some other performers said that felling nervous at first but it can be overcome by learning by understanding the topic and practice repeatedly.